Impact of green and low-carbon technological innovation on green total factor productivity of industrial sector: An analysis based on BAM-DEA model - Yuechi Zhang; Zhuang Miao; Yangyang Sun (Sustainable Futures)
Green and low-carbon technological innovation is an important engine for the sustainable and high-quality development of the industrial sector. The implementation of green and low-carbon technological innovation, as a means of supporting relevant policies, is crucial to the effective realization of China's dual-carbon goals. To explore the intrinsic relationship between green and low-carbon technological innovation and green total factor productivity, this study adopts data from 38 industrial sectors in China from 2005 to 2020, and measures green total factor productivity by using the BAM-DEA model, and explores the impact of green and low-carbon technological innovation on industrial green total factor productivity by two-way fixed-effects model. Furthermore, this study further explores the moderating effects of R&D funding investment and R&D personnel investment as moderating variables on the relationship between green and low-carbon technological innovation and industrial green total factor productivity. The results indicate that the green and low-carbon technological innovation can significantly promote green total factor productivity of 38 industrial sectors, and endogeneity test and robustness test indicate that the results are robust. R&D funding investment and R&D personnel investment play important moderating effect on the relationship between green low-carbon technological innovation and green total factor productivity. Additionally, heterogeneity analysis shows that the impact of green and low-carbon technological innovation on green total factor productivity is particularly significant in the non-high carbon emissions and high-tech industries. This study aims to provide empirical evidence for promoting high-quality development and green low-carbon transformation in China's industrial sector.